Tekanan Darah Pasien Stroke yang Mendapat Latihan Range of Motion (ROM) di Ruang Bougenvile RSD Mardi Waluyo Blitar - Aldonna Mariana (STIKes Patria Husada Blitar, 2014)
Range Of Motion (ROM) is an action that can be perfomed on stroke patients to prevent muscle and joint stiffness. The purpose of this study was to describe blood pressure in stroke patients who received exercise Range Of Motion (ROM) in the RSD Mardi Waluyo Blitar. Method: Research design was descriptive design. The population in this study is that stroke patients treated in Bougenvile RSD Mardi Waluyo Blitar in 2013 as many as 590 and the average monthly total of 49 stroke patients. Research sample was 33 patients. Its choosed by Â using purposive sampling technique. Data collection is done by measuring blood pressure and exercise to train Range Of Motion (ROM). Time data collection was done on April 1st until Â 26th , 2014. Result: The results showed that blood pressure in stroke patients after getting a training Range Of Motion (ROM) 39.4% (13 respondents) had increased, 30.3% (10 respondents) had decreased and consistent after getting a training Range Of Motion (ROM). Discussion: Recommendations from this study are expected to be more vigilant in monitoring stroke patients trained Range Of Motion (ROM).Â